Understanding Factors Influencing Whole-Process Consulting Service Quality: Based on a Mixed Research Method - Qinghong Cui; Haoran Zhao; Haiyang Zhang; Xiancun Hu; Guangbin Wang (Buildings)
To address the fragmentation in the engineering consulting industry, whole-process consulting (WPC) has undergone rapid development in China. Engineering consulting companies are actively transitioning towards WPC and aiming to enhance whole-process consulting service quality (WPCSQ). However, research on WPCSQ and its influencing factors is still lacking. This paper adopts a mixed research approach combining qualitative and quantitative methods. Initially, the grounded theory (GT) method is used to determine the influencing factors of WPCSQ, and the TEOK model is constructed. Then, Partial Least Squares Structural Equation Modeling (PLS-SEM) is utilized for model validation. The results show that WPCSQ is most affected by knowledge management and least affected by organizational factors. Based on the above analyses, recommendations for improving WPCSQ are provided from the viewpoints of engineering consulting companies and governments. These suggestions are aimed at fostering the healthy and sustainable progression of WPC.